Identification of heat tolerant lentil genotypes through stress tolerance indices - Rohit Sarkar; Gyan Prakash Mishra; Premakumar; Ankita Singh; Jenia Roy; Kumbarahally Murthigowda Shivaprasad; Shashidhar B. Reddappa; Sudhir Kumar; Ruchi Bansal; Uttarayan Dasgupta; Soma Gupta; Susheel Kumar Sarkar; et al. (Scientific Reports)
Abstract With climate change projections indicating an increase in the frequency of extreme heat events and irregular rainfall patterns globally, the threat to global food security looms large. Terminal heat stress, which occurs during the critical reproductive stage, significantly limits lentil productivity. Therefore, there is an urgent need to improve lentil’s resilience to heat stress to sustain production. However, studies identifying heat-tolerant sources in lentils are limited. To address these issues, we assessed 158 lentil genotypes under normal and late-sown conditions over two consecutive seasons. We employed eleven heat stress indices to identify lines tolerant to heat stress. All genotypes exhibited a decrease in average grain yield when subjected to stress conditions as compared to non-stress conditions, indicating the impact of heat stress on crop yield. Correlation analysis showed significant positive correlation between yield in normal and late-sown conditions and the following heat stress indices: STI, MP, MRP, YI, GMP, and HM. In contrast, TOL, SSPI, and PYR showed negative associations with yield in late-sown conditions. Based on these indices, we identified the genotypes P13143, P13130, and P13135 as high-yielding in both stress and non-stress conditions. Cluster analysis and biplot display in PCA also confirmed that genotypes P13143, P13130, and P13135 exhibited suitability and high yield potential in both environments. These genotypes can be utilized as donors in future breeding programs to introduce genetic variations for improving heat stress tolerance in lentil.